2013
DOI: 10.1175/jcli-d-12-00053.1
|View full text |Cite
|
Sign up to set email alerts
|

Inactive Period of Western North Pacific Tropical Cyclone Activity in 1998–2011

Abstract: Tropical cyclone (TC) activity over the western North Pacific (WNP) exhibits a significant interdecadal variation during 1960-2011, with two distinct active and inactive periods each. This study examines changes in TC activity and atmospheric conditions in the recent inactive period (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011). The overall TC activity shows a significant decrease, which is partly related to the decadal variation of TC genesis frequency in the southeaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
145
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(177 citation statements)
references
References 22 publications
23
145
2
Order By: Relevance
“…The variations of TC genesis frequency and intensity in the WNP, from intraseasonal to interdecadal time scales, are related to ISO phases (e.g., Gray 1979;Huang et al 2011;Li and Zhou 2013;, monsoon trough variability (e.g., Ritchie and Holland 1995;Chen et al 2004;Wu et al 2012), the El Niño-Southern Oscillation (e.g., Chan 2005;Du et al 2011;Kim et al 2011), and the PDO (e.g., Yang et al 2012;Liu and Chan 2013). WNP TC genesis frequency depends on the ISO phase ) and might also vary with different climate backgrounds of the EASM (Zhou et al 2009;Wang et al 2012) and PDO phase (Liu and Chan 2013).…”
Section: Did Anthropogenic Climate Change Influence the Extreme Tc Acmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations of TC genesis frequency and intensity in the WNP, from intraseasonal to interdecadal time scales, are related to ISO phases (e.g., Gray 1979;Huang et al 2011;Li and Zhou 2013;, monsoon trough variability (e.g., Ritchie and Holland 1995;Chen et al 2004;Wu et al 2012), the El Niño-Southern Oscillation (e.g., Chan 2005;Du et al 2011;Kim et al 2011), and the PDO (e.g., Yang et al 2012;Liu and Chan 2013). WNP TC genesis frequency depends on the ISO phase ) and might also vary with different climate backgrounds of the EASM (Zhou et al 2009;Wang et al 2012) and PDO phase (Liu and Chan 2013).…”
Section: Did Anthropogenic Climate Change Influence the Extreme Tc Acmentioning
confidence: 99%
“…WNP TC genesis frequency depends on the ISO phase ) and might also vary with different climate backgrounds of the EASM (Zhou et al 2009;Wang et al 2012) and PDO phase (Liu and Chan 2013). Previous studies suggested that the modulation of TCs by the ISO during July-August of 1979-2008 or 1979-2004 was relatively weak compared to other seasons Kim et al 2008).…”
Section: Did Anthropogenic Climate Change Influence the Extreme Tc Acmentioning
confidence: 99%
“…Yeh et al (2010) showed a decadal relationship between the TC frequency and tropical Pacific SST, with a positive correlation during the period 1990-2000 but a negative correlation during the period 1979-89. Liu and Chan (2013) examined changes in TC activity and atmospheric conditions during 1998-2011. TC activity shows a significant decrease, which is partly related to the decadal variation of the TC genesis frequency in the southeastern part of the WNP.…”
Section: Introductionmentioning
confidence: 99%
“…The variations of TC genesis frequency and intensity in the WNP, from intraseasonal to interdecadal time scales, are related to ISO phases (e.g., Gray 1979;Huang et al 2011;Li and Zhou 2013;Yang et al 2015), monsoon trough variability (e.g., Ritchie and Holland 1995;Chen et al 2004;Wu et al 2012), the El Niño-Southern Oscillation (e.g., Chan 2005;Du et al 2011;Kim et al 2011), and the PDO (e.g., Yang et al 2012;Liu and Chan 2013). WNP TC genesis frequency depends on the ISO phase (Huang et al 2011) and might also vary with different climate backgrounds of the EASM (Zhou et al 2009;Wang et al 2012) and PDO phase (Liu and Chan 2013).…”
Section: Did Anthropogenic Climate Change Influence the Extreme Tc Acmentioning
confidence: 99%
“…WNP TC genesis frequency depends on the ISO phase (Huang et al 2011) and might also vary with different climate backgrounds of the EASM (Zhou et al 2009;Wang et al 2012) and PDO phase (Liu and Chan 2013). Previous studies suggested that the modulation of TCs by the ISO during July-August of 1979-2008 or 1979-2004 was relatively weak compared to other seasons (Huang et al 2011;Kim et al 2008).…”
Section: Did Anthropogenic Climate Change Influence the Extreme Tc Acmentioning
confidence: 99%